Penegakan Hukum Terhadap Fenomena “Endorsement” Situs Judi Online Oleh Selebgram Di Kepolisian Daerah Bali - I Made Handariantika Nugraha; I Wayan Wahyu Wira Udytama (Jurnal Hukum Mahasiswa, 2026)
Online gambling businesses utilize social media influencers who provide paid endorsement and marketing services. These influencers promote their sites with the promise of lucrative payments. Article 45 paragraph 3 of Law Number 1 of 2024 regulates advertising for online gambling companies. Using an empirical legal research approach, this study relies on data collected from interviews and field observations. This study uses a descriptive approach to explain the current situation of the phenomenon related to the law enforcement efforts of the Bali Police Cyber Investigation Directorate. The study concludes that law enforcement is carried out through online patrols, monitoring accounts, conducting investigations, managing investigations, and then sending suspects and evidence to the prosecutor's office for legal proceedings. Obstacles in the enforcement process include internally the lack of tools to directly block online gambling sites and externally the low level of legal awareness in the community.